Antitumor Effect and Immune Response of Nanosecond Pulsed Electric Fields in Pancreatic Cancer - Zhao, Jing; Chen, Shuochun; Zhu, Lu; Zhang, Liang; Liu, Jingqi; Xu, Danxia; Tian, Guo; Jiang, Tian’an (Frontiers in Oncology, 2021)
Nanosecond pulsed electric fields (nsPEFs) have emerged as a novel and effective strategy for the non-surgical and minimally invasive removal of tumors. However, the effects of nsPEFs treatment on the tumor immune microenvironment remain unknown. In this study, the changes in the morphology and function of pancreatic cancer cells after nsPEFs were assessed and the modifications in the immune profile in pancreatic cancer models were investigated. To this end, electrodes were inserted with different parameters applied to ablate the targeted tumor tissues. Tumor development was found to be inhibited, with decreased volumes post-nsPEFs treatment compared with control tumors (P < 0.05). Hematoxylin and eosin staining showed morphological changes in pancreatic cancer cells, Ki-67 staining confirmed the effects of nsPEFs on tumor growth, and caspase-3 staining indicated that nsPEFs caused apoptosis in the early stages after treatment. Three days after nsPEFs, positron emission tomography demonstrated little residual metabolic activity compared with the control group. Gene expression profiling identified significant changes in immune-related pathways. After treatment with nsPEFs , CD8+ T lymphocytes increased. We showed that nsPEFs led to a significant decrease in immune suppressive cells, including myeloid derived suppressor cells, T regulatory cells, and tumor-associated macrophages. In addition, the levels of TNF-α and IL-1β increased (P < 0.05), while the level of IL-6 was decreased (P < 0.05). NsPEFs alleviated the immunosuppressive components in pancreatic cancer stroma, including hyaluronic acid and fibroblast activation protein-α. Our data demonstrate that tumor growth can be effectively inhibited by nsPEFs in vivo. NsPEFs significantly altered the infiltration of immune cells and triggered immune response.